Factors Affecting Chronic Heart Failure in Patients with End-Stage Renal Disease at Bhayangkara Hospital Denpasar - Ni Gusti Ayu Putu Lestari Santika Dewi; A. A. Ayu Dwi Adelia Yasmin; Ni Made Citra Riesti Wulan; I Gede Catur Wira Natanagara (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2022)
Background: Patients with end-stage renal disease (ESRD) have a twofold risk of developing heart failure. A number of factors in ESRD patients are related to chronic heart failure (CHF). The intervention of cardiovascular risk factors in the early stages of chronic kidney disease (CKD) can reduce mortality from heart disease and slow the severity of kidney deterioration. This study aims to examine the factors that affect CHF in patients with ESRD. Methods: This study was a cross-sectional analytic observational study of 49 patients with ESRD based on consecutive sampling. The data collected were primary and secondary data on ESRD patients at the Cardiac Polyclinic, Internal Medicine Polyclinic, and the Medical Records Unit Bhayangkara Hospital Denpasar. Results: In this study, it was found that most patients were in the age group ≥40 years (92%) and male gender (63%). From the chi-square test analysis, it was found that the factors affecting CHF in patients with ESRD are hypertension (HT) (p-value < 0.001) with prevalence ratio (PR) 11.19 (1.69-73.92), type 2 diabetes mellitus (T2DM) (p-value = 0.008) with PR 1.72 (1.18-2.51), obesity (p-value < 0.001) with PR 6.67 (2.34-18.92), and smoking (p-value = 0.027) with PR 1.6 (1.02-2.49). Conclusion: It can be concluded that the factors affecting CHF in patients with ESRD are HT, T2DM, obesity, and smoking. The results of this study are expected to be used as an illustration so that in the future, prevention can be made for factors affecting CHF in ESRD patients.